Design of A Career Problem-Based Cunseling Service Program for Students Reviewing from Career Readiness - Dwi Putri, Besti Nora; Suyadi, Suryadi; Nofridayati, Sesi (Holistic Science, 2022)
This research is motivated by the phenomenon that there are still students who still don't understand what a career is, there are still students who don't care about careers, there are still students who can't choose a career or their future and there are still those who don't know how to achieve a good career. success. The aims of this research are 1) to describe career problems for high school students, 2) to design a Guidance and Counseling Service Program based on career problems for high school students. This research was conducted using a quantitative descriptive method. The population and sample in this study amounted to 199 students, the sample was taken using a total sampling technique. The instrument used is a questionnaire. As for the data analysis using the percentage technique. The results of the research generally show that the career problems of high school students are in the high category. From these results, a program of guidance and counseling services will be designed in the form of information services, group guidance services, consulting services. This research is recommended for high school students who will prepare themselves. for his career.